MOTIVATION OF NON-MADRASA GRADUATES IN STUDYING ARABIC AT DEPARTMENT OF ARABIC LANGUAGE EDUCATION, STATE ISLAMIC INSTITUTE, KENDARI / Ø¯ÙˆØ§ÙØ¹ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø®Ø±Ù‘ÙŠØ¬ÙŠÙ‘ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø¹Ø§Ù…Ø© ÙÙŠ Ø´Ø¹Ø¨Ø© ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Rachmad Ramadhan; Kamilatul Ubudiyah (IAIN Batusangkar, Indonesia, 2022)
The purpose of this study is to determine the motivation of non-madrasa graduate students to learn Arabic at Department of Arabic Language Education of IAIN Kendari. The type of this research was descriptive qualitative in which data were collected by observation, interview, and documentation. The source of primary data was the non-madrasa graduates who study at Arabic language education and the secondary data was the lecturers. Data were analyzed by reducing, displaying, drawing conclusion. The result of the study indicated that the students’ motivation to study at Arabic Language Department was varied. Their internal motivation was the desire to learn a new thing, to become a professional Arabic teacher, and to learn the language of Qur’an in order to understand its contents. Their external motivation came from their parents’ advice, the enjoyable learning experience of Arabic at their previous educational level, and coming from a family where they regularly speak Arabic. Encouragement from within and peers, interesting learning media, and the instructional approach were all factors that encourage them to learn Arabic at the Arabic Language Education Department. On the other hand, their lack of basic Arabic proficiency, laziness, and a less accommodating language environment are the main barriers for some learners.